A Novel Smart Shopping System With New Payment Solution at Mini-Mart - Nguyen, Hoai-Nhan (Journal of Technical Education Science, 2025)
This paper presents a novel smart shopping system. This is a solution for an automatic purchasing equipment for mini-marts with integration of a QR code payment method. A system consists of a vending box (a touch screen, a computer), a store, customer baskets, wifi connection and a methodology of QR code payment. The customer orders a set of good items by interacting with a vending box via the touch screen, using non-cash payment method, and then waiting for the bank confirmation of receiving of money via the internet, finally, the system carries the selected items to the customer ‘s shopping basket by automatic transporting systems. The QR code payment method increases the convenience, the transaction speed, the ease of use, and time-saving; even reduces the risk of carrying cash and storing cash in the machine (for the owner). Many experiments were conducted to show the effectiveness and the performance of the proposed system.